Múltiplas visões sobre as atividades de trabalho remunerado, desenvolvidas na Penitenciária Estadual de Maringá - Moreira Neto, Alfredo Lopes da Costa (2006)
The present work of research has directed efforts on understanding the multiple opinions, about work, from the people involved in the profitable activities developed in Maringá State Prison. The main objective was to prove, on prison work among the involved people and also to analyze if this work gathers the characteristics presented by Arendt (2004), in relation to what he calls vita activa, represented by the fundamental human activities called labor, work and action, in the involved people's opinion. It was necessary to revise the literature on the work, and also on the total institutions characteristics, where prisons fit. The demanded data was collected through interviews with the people involved in this investigation, always with the necessary methodological strictness. Proceeding to the respective analysis and data interpretation, some conclusions were drawn, such as: the opinions about prisoners work are multiple, and its characteristics, basically match with Arendt's labor.